Tandem Condensation‐Hydrogenation to Produce Alkylated Nitriles Using Bifunctional Catalysts: Platinum Nanoparticles Supported on MOF‐Derived Carbon. Issue 2 (18th December 2019) - Huang, Ao; Nie, Renfeng; Zhang, Biying; Pei, Yuchen; Chen, Minda; Behera, Ranjan; Yu, Jiaqi; Luan, Xuechen; Hunter, Nicholas T.; Ke, Ming; Huang, Wenyu
Abstract: Tandem catalysis, which allows multiple steps of a reaction to take place without the need for separation and purification, is highly desired for the design of efficient and environmentally‐friendly chemical processes. Herein, the pyrolysis of UiO‐66‐NH2, an amino‐functionalized metal‐organic framework, produces nitrogen‐rich carbon‐ZrO2 composite (CN‐ZrO2 ). This composite is rich in basic sites and effectively catalyzes the Knoevenagel condensation reaction. After loading Pt nanoparticles onto this composite support, a tandem catalyst (Pt/CN‐ZrO2 ) is produced to be capable of the one‐step Knoevenagel condensation‐hydrogenation reaction to produce an alpha‐alkylated nitrile. The tandem catalyst exhibits >99 % aldehyde conversion and >99 % selectivity toward alpha‐alkylated nitrile under 1 MPa H2 at 80 °C. This catalyst could be reused for five times in the presence of malononitrile without significant deactivation and is versatile for one‐step condensation‐hydrogenation of various aldehydes. The good performance of Pt/CN‐ZrO2 could be ascribed to the synergistic interaction between Pt and CN‐ZrO2 composite supports that lead to the appropriate hydrogenation activity of supported Pt nanoparticles. Abstract : Nanocatalyst for tandem reactions : The development of the recyclable bifunctional catalyst Pt/CN‐ZrO2 can effectively catalyze a one‐step tandem Knoevenagel condensation‐hydrogenation reaction by loading Pt nanoparticles on an amino‐functionalized MOF onto N‐doped carbon. The Pt/CN‐ZrO2 catalyst exhibited excellent catalytic property. This work opens up new avenues for the synthesis of bifunctional metal‐N‐doped carbon hybrid catalysts for tandem catalysis.